Asymptotic behavior of oscillatory solutions of first order functional delay difference equations - Murugesan, A.; Soundara Rajan, C. (International Journal of Applied Mathematical Research, 2015)
In this paper, we study the asymptotic behavior of oscillatory solutions of the first order functional delay difference equationequation* Δ x(n)=f(n, x(n-τ)),n≥ n_0. (*)equation*A new sufficient condition is established under which every oscillatory solution of (*) tends to zero asymptotically.